Kajian Potensi Fisik Dan Non Fisik Menuju Pengembangan Desa Tertinggal Di Kecamatan Seluma Utara Kabupaten Seluma - Mirna Yunita; Warsa Sugandi Karman; Fevi Wira Citra; Muhammad Alfi; Riki Nopiansyah; Dedi Guntar; Yuneva Yuneva; Winda Ade Ariani (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2021)
Seluma Utara sub-district is one of the areas whose villages are classified as underdeveloped and even quite apprehensive, the three villages that are categorized as quite apprehensive are Sikalak Village, Sinar Pagi, and Talang Banyan Village, based on the results of observations and interviews, the cause of the lagging of these three villages is road access that has not There is still sufficient clay, the low level of public education, natural resources that are not managed properly, and the absence of electricity, this causes difficulties in carrying out activities. The study of physical and non-physical potential is a method that can be used to develop a strategy for developing underdeveloped villages in North Seluma District, especially in three villages, namely Sikalak Village, Sinar Pagi and Talang Banyan Village. The findings obtained are: 1) physical potential: a) the land is used for agriculture and contains mineral coal; b) cold climate; c) highlands; d) the majority of the community, apart from farming, also raise poultry for their daily needs and to sell them; 2) Non-physical potential: a) the distance traveled by people who will travel from the village is very far and there is no transportation that can transport people outside the village but using their own vehicle; b) road facilities that are quite apprehensive are obstacles for the community to enter and exit the village; c) other infrastructure facilities such as education and health are not available in the area. From these findings, strategies for developing underdeveloped villages in the North Seluma region can be drawn up in particular: 1) conduct socialization in various fields; 2) carry out training and empowerment of agriculture and livestock in the community. build 3) village road facilities that connect with other areas; 4) build a power grid; 5) build educational facilities; 6) build health facilities; 7) build a traditional hall.